Immune-phytopathological assessment of resistance of wheats to stem rust in conditions of the Southeast of Kazakhstan - Gabdulov, M. A.; Kochorov, A. S.; Karakaya, A.; Morgunov, A. I.; Karbozova, R. D.; Amangeldikyzy, Z. (My University, 2019)
The paper presents the results of the immunological evaluation of the varieties of spring wheat of the 17F1SYNT-OMSK-LIST farm: 90 samples and 7 susceptible local varieties jointly created by scientific institutions of Kazakhstan, Western Siberia and the CIMMYT International Wheat and Maize Improvement Center in conditions of the southeast of Kazakhstan. The study was conducted in 2016-2017 on natural and artificial infection background using field and laboratory methods. The varieties of spring and winter wheats sustainable and susceptible to stem rust for selection on immunity have been isolated 6 varieties are sustainable to stem rust, namely: LINE-N-19SB, LUTESTSENS7-04-4, CARBERRY, URALOSYBIRSKAYA, ERITROSPERMUM 85-08 and LYUTESTSENS 6-04-4.From winter wheats have been isolated of resistance 19 lines and the genes Sr2, Sr22, Sr24, Sr26, Sr36. These valuable genotypes will be recommended for use in selection as a valuable source material in releasing stem rust resistant varieties in the future. работе представлены результаты иммунологической оценки сортов яровой пшеницы фермы 17F1SYNT-OMSK-LIST: 90 образцов и 7 восприимчивых местных сортов, совместно созданные научными учреждениями Казахстана, Западной Сибири и Международного центра улучшения пшеницы и кукурузы CIMMYT. в условиях юго-востока Казахстана. Исследование проводилось в 2016-2017 гг. На фоне естественной и искусственной инфекции с использованием полевых и лабораторных методов. Выделены сорта яровой и озимой пшеницы, устойчивые и восприимчивые к стеблевой ржавчине, для селекции на иммунитет. 6 сортов, устойчивых к стеблевой ржавчине, а именно: LINE-N-19SB, LUTESTSENS7-04-4, CARBERRY, URALOSYBIRSKAYA, ERITROSPERMUM 85-08 и LYUTESTSENS 6-04-4. Из озимой пшеницы были выделены линии устойчивости 19 и гены Sr2, Sr22, Sr24, Sr26, Sr36. Эти ценные генотипы будут рекомендованы для использования при селекции в качестве ценного исходного материала для выпуска устойчивых к стеблевой ржавчине сортов в будущем. V rabote predstavleny rezul'taty immunologicheskoy otsenki sortov yarovoy pshenitsy.
ECOLOGY, ENVIRONMENT AND CONSERVATION
Keywords: зерновые культуры; научный журнал; яровая пшеница; периодическое издание; озимая пшеница; скопус; импакт-фактор 2018; зарубежное издание; дальнее зарубежье